New species and records of Heterospio (Annelida, Longosomatidae) from continental shelf, slope and abyssal depths of the Atlantic Ocean, Pacific Ocean, Indian Ocean and adjacent seas - Blake, James A.; Maciolek, Nancy J. (Zootaxa, 2023)
Nineteen species of the rare polychaete genus Heterospio are reported, 15 of which are new to science. The status of H. longissima Ehlers, 1874, the type-species, is reviewed. The specimens examined are from several locations in the North Atlantic Ocean, Gulf of Mexico, Caribbean Sea, off Br azil, the Indian Ocean, the Pacific Ocean off California, New Zealand, Australia, and the South China Sea. Deep-water samples from the western North Atlantic Ocean collected by the late Drs. H.L. Sanders and R.R. Hessler that were reported by Hartman as H. longissima were re-examined and referred to two new species, H. hartmanae n. sp. (abyssal depths, New England to Bermuda transect) and H. guiana n. sp. (bathyal depths off Suriname). Other materials from the Sanders/Hessler North Atlantic collections were also examined and referred to two additional species, H. canariensis n. sp. (deep water off Canary Islands) and H. southwardorum n. sp. (Bay of Biscay) as well as H. cf. reducta from off SW Ireland in bathyal depths. New collections from the North Atlantic region include additional materials of H. hartmanae n. sp. (deep water off the Mid-Atlantic and SE USA), H. aruba n. sp. (Caribbean Sea), H. bathyala n. sp. (deep water off SE USA), and H. dibranchiata n. sp. (deep water, Gulf of Mexico). Heterospio paulolanai n. sp. is from shelf depths off southeastern Brazil. Heterospio knoxi n. sp. is from the North Island of New Zealand, H. ehlersi n. sp. is from the Gulf of Thailand, in the South China Sea, H. bidentata n. sp. is described from deep water in the Coral Sea off eastern Australia, and H. alata n. sp. and H. brunei n. sp. are described from deep water off the Island of Borneo in the South China Sea. Heterospio africana n. sp. and H. antonbruunae n. sp. are described from off east Africa in the Mozambique Channel. New records and descriptions of H. catalinensis, H. indica, and H. peruana are presented. The 15 new species reported here nearly triple the number of previously known species of Heterospio, with 23 species now recognized. All known species are tabulated and compared.